Perilaku Binturong (Arctictis binturong) di Pusat Penyelamatan Satwa (PPS) Alobi, Provinsi Bangka Belitung - Anggraeni, Anggraeni; Shabirah, Fauziyah; Fauziyah, Zaenab; Nandi, Febbi Julia; Pramudita, Ratri; Citra, Munica Ade (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2023)
Binturong (Arctictis binturong) is an animal in the Viverridae family and one of the endangered species. The research was conducted at the Alobi Animal Rescue Center (PPS) from April 27-30 2023. The Alobi Wildlife Rescue Center (PPS) is a special conservation organization located in Bangka Belitung Province. The aim of this study was to analyze and identify the behavior of the Binturong animal (Arctictis binturong) in the Alobi PPS area. The research used direct observation methods, behavior sampling, interviews and data analysis. The animal objects observed were three binturongs, namely male binturongs (Wembi and Bembi) and female binturongs (Maya). The results obtained during the study were the highest locomotion activity in Maya with a frequency of 233, and the lowest locomotion activity in Bembi with a frequency of 74.5. Then, the highest grooming was in Maya with a frequency of 34 and the lowest in Bembi 26 followed by the highest eating and drinking activities in Maya with a frequency of 18 and the lowest in Bembi 2. The highest social activity was in Bembi 13.5 and the lowest in Wembi was 0. The activity of breaking off the highest frequency i.e. 77 in Maya and the lowest in Bembi 9. The highest sequential frequency value is 0,5 urination in Maya, and the highest defecation is 1 in Bembi. The highest frequency for timber violations was Wembi, which was 41, and the lowest was Bembi, 4.5. the highest frequency vocalization behavior is on Maya 4.5 and the lowest is on Bembi 0.